Stock Market Awareness among Female Investors: A Study in Pokhara, Nepal - Dhungana, Bharat Ram; Giri, Nisha; Ojha, Deepak; Ranabhat, Deepesh; Lamichhane, Keshav; Acharya, Sujana (Journal of Business and Social Sciences Research, 2025)
This study explores stock market awareness among female investors in Pokhara, Nepal, highlighting the key factors that influence their investment decisions. Using data from 180 respondents analysed through descriptive statistics, correlation, and regression, the study finds that financial literacy, financial access, income source, and information access significantly affect investor awareness, while family status has little impact. The results emphasize that enhanced financial knowledge and inclusion can empower women to make informed investment choices and achieve better stock market returns. The study recommends that regulatory authorities and policymakers implement targeted financial literacy programmes and improve financial inclusion to boost female participation in Nepal’s capital market.